Comparison of a continuous and intermittent triangular protocols for direct VO2max assessement - Cardoso, Carla (2018)
The purpose of this study was to compare two incremental protocols for V02max assessment and minimum swimming velocity that elicits V02max (vV02max). The sample comprised 11 Portuguese swimmers: 6 females (2 1.00± 1. 79 years, 54.83±3.71 kg, and 163.83±1.47 cm) and 5 males (25.40±2.79 years, 69.00±9.03 kg, and 175.00±9.03 cm). They performed two incremental protocols (starting at 0.9 m.s'\ with increments of 0.05 m.s,l per 200-m stage) for freestyle V02max assessment, with a 48h interval and in the same general conditions. One protocol was a continuous test and the other an intermittent one, with 30-s rest between incremental stages for [La-] assessment. Mean values of V02max, vV02max, VE, R, HR and [La-] for continuous and intermittent protocol, were respectively 52.5±9.44 m1.kg'l.min'l and 53.4±8.74 rnl.kg'l.min'l, 1.16±O.099 m.s) and 1.15±O.099 m.s-l, 95.3±26.32l.min,l and 95.8±26.60 l.min'l, 1.00±0.044 and 1.00±0.053, 183.l±9.47b.min'l and 187.5±8.44 b.min'l, 7.36±Ll313mM.rl and 8.86± 1.93hnM.r1. [La-] was the only different parameter between both protocols (p 0.05). Resnlts pointed out that both protocols were suitable for V02max and vV02max assessment in swimming.